ANALISIS KOMPARATIF TINGKAT KESEHATAN BANK ANTARA CAMELS DAN RGEC PT. BANK BPD BALI TAHUN 2012-2014 - Brahmananda, Ida Bagus; Suputra, I.D.G Dharma (E-Jurnal Akuntansi, 2017)
This study aimed to compare the health level of PT. Bank BPD Bali using CAMELS method and RGEC. This research is descriptive with quantitative approach. The object of this research is financial statements. Regional Development Bank Bali 2012-2014. Data collection techniques of research done by downloading the financial statements of the official website of PT. Regional Development Bank Bali. The analysis technique used is descriptive comparative method to determine the soundness of a bank to be classified into the health of banks. The study states that the level of Health PT. Bank BPD Bali using CAMELS method and RGEC, shows the title of the bank in accordance with the standards set by Bank Indonesia late, the average PT. Bank BPD Bali predicate very healthy in 2012-2014.
Keywords: CAMELS, RGEC